Antibiotic use practices of pharmacy staff: a cross-sectional study in Saint Petersburg, the Russian Federation - Belkina, Tatiana; Duvanova, Natalia; Karbovskaja, Julia; Tebbens, Jurjen Duintjer; Vlcek, Jiri (BMC pharmacology & toxicology, 2017)
BACKGROUND: Non-prescription access to antimicrobials is common, and self-prescribing is increasingly popular in Russian society. The aim of this study was to assess the attitudes of community pharmacists regarding antibiotic use and self-medication. METHODS: We conducted a cross-sectional study from September-December 2015 of community pharmacists in the Saint-Petersburg and Leningrad region, Russia. A self-administered questionnaire was used to assess antibiotic use and self-medication practices. The data were analysed using logistic regression and Pearson chi-squared tests. RESULTS: Of the 316 pharmacists (77.07%) who completed the questionnaire, 230 (72.8%) self-medicated with antibiotics. Antibiotics were mostly used to self-treat upper (53.3%) and lower respiratory tract infections (19.3%), relying on their own knowledge (81.5%), previous treatment experience (49%) and patients' prescriptions (17%). The most commonly used antibiotics were macrolides (33.2%). Characteristics such as age, education and experience were related to antibiotic use and self-medication. CONCLUSIONS: The study confirmed that self-prescription of antibiotics is a common practice amongst pharmacists in Saint Petersburg and also identified personal and professional characteristics of pharmacists strongly associated with self-medication.
Keywords: Self Medication; Russia; Cross-Sectional Studies; Anti-Bacterial Agents; zpráva o sobě; Attitude of Health Personnel; Antimicrobial resistance; Rusko; Middle Aged; mužské pohlaví; průřezové studie; Adult; mladý dospělý; postoj zdravotnického personálu; Self Report; Young Adult; Antibiotic use; ženské pohlaví; Humans; Pharmacies; farmaceuti; lékárny; antibakteriální látky; lidé středního věku; dospělí; Female; Pharmacists; samoléčba; lidé; Male